(3QjMGf GdCdHGH, hQjYGf GdTHGH, aj eQGJH GdBOGHs - (3eMeO Hf EHQGgje Hf NjQI, CHh GdbGSe Hf GdehGYjfj GdbQWHj GdETHjdj,J (B564 (3g` s
(3ChdgG (B:s
(3QH ChRYfi Gf CTcQ fYeJc GdJi GfYeJ Ydi gPG cJGH febJg HELJeGY GdacQ s
(3BNQgG (B:s
(3aVd GdRgGO hGdeHJdjf, bGd Ydi Hf CHj WGdH(B: (3bfY GdfaS dcaGa hEdG WdHJ efc ahb eG jcajgG hEfeG GfJ Whd YeQc eGYeQ J ai GdSGYI GdJi CfJ ajgG hGdMeO ddgced JCdjag s
(3GdfSNI HgG MhGTs
(3GfXQ GdLRA GdChd Qbe (B437 (3COHs
(3HChdgG agQS ddehVhYGJ s
(3Cced JCdjaI (B557(3g`s
(3hYdi MhGTjgG HYV GdJbjjOGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs